ANALISIS PENGARUH JUMLAH KUNJUNGAN WISATAWAN, JUMLAH OBJEK WISATA DAN TINGKAT HUNIAN HOTEL TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus Pemerintah Kabupaten Karanganyar) - Hesty Maharani; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
Regional original income is revenue sourced from the region. Thepurpose of this study was to determine (1) The effect of the number of touristvisits on local revenue (2) The effect of the number of tourist objects on localrevenue (3) The effect of hotel occupancy rates on local revenue. This study usessecondary data in the form of local revenue data, the number of tourist visits, thenumber of attractions, and hotel occupancy rates. The population in this study isKaranganyar district during the period 1998-2018. The sampling technique inthis study uses the saturated sample method. This study uses multiple linearregression analysis techniques with the results of the study showing that thenumber of tourist visits has no effect on local revenue, the number of attractionshas an effect on regional income, and hotel occupancy rates have no effect onregional income.